2023
DOI: 10.1088/2515-7655/acb28f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the light-induced oxygen vacancy in the photochemical conversion

Abstract: The formation of light-induced oxygen vacancy (VO) is detected and confirmed on the surface of various metal-oxide-based semiconductors under mild reaction conditions with low cost energy source (sunlight). This self-structural transformation of the materials can bring about new characteristics and functionalities, which has inspired many researchers to explore the applications of light-induced VO in the photochemical conversion. In this perspective, generating and maintaining the light-induced VO are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…By fitting the temperature dependence of the polarization decay rate to a two-phase exponential model and extracting the activation energy (Figure S15), we can deduce that the slow recovery dynamics are likely related to the diffusion of charged defects, such as oxygen vacancies [49]. During UV illumination, both intrinsic and additional light-induced oxygen vacancies [46,47,48] can contribute to the pinning of the transient out-of-plane polarization. In the dark, the recovery of the depolarized state is subsequently governed by the diffusion-limited redistribution of oxygen vacancies [49].…”
Section: Resultsmentioning
confidence: 99%
“…By fitting the temperature dependence of the polarization decay rate to a two-phase exponential model and extracting the activation energy (Figure S15), we can deduce that the slow recovery dynamics are likely related to the diffusion of charged defects, such as oxygen vacancies [49]. During UV illumination, both intrinsic and additional light-induced oxygen vacancies [46,47,48] can contribute to the pinning of the transient out-of-plane polarization. In the dark, the recovery of the depolarized state is subsequently governed by the diffusion-limited redistribution of oxygen vacancies [49].…”
Section: Resultsmentioning
confidence: 99%
“…Surface defect engineering 33 and co-catalyst engineering 34 have important applications in photothermal catalytic CO 2 reduction reactions 35 . In addition to bringing about alterations in the band gap and electronic structure, thereby changing the radiation absorption and conversion performance of the material, the introduction of oxygen vacancies can also function as reaction active sites for the adsorption and activation of surface species during the catalytic process 36,37 . Similarly, the incorporation of metal oxides and the loading of nanometal particles can further create tailored functional sites on the material surface, enhancing the selective adsorption and activation of reactants and facilitating the subsequent reduction of key intermediates 38,39 .…”
mentioning
confidence: 99%
“…Studies in the field of photocatalysis have shown that illumination can cause semiconductor materials to discharge lattice oxygen, generating O 2 gas. In the two-step photothermal chemical cycle, a thermal reaction allows materials to consume oxygen vacancies and react with water to produce hydrogen. , Simultaneously, a light reaction enables the material to release oxygen and regenerate oxygen vacancies, thus forming a cycle. This approach of maintaining a high state of oxygen vacancies in materials through direct illumination is called the photoinduced oxygen vacancy pathway. Moreover, materials rich in oxygen vacancies demonstrate a superior photocatalytic performance compared to their bulk counterparts. , This pathway, if applied to SOECs, holds promise for improving the oxygen distribution at the anode, thereby addressing cell degradation issues.…”
mentioning
confidence: 99%